6x + 2y = -88
2y = -88 -6x
y=-88/2 -6/2x
y= -44 - 3x
y = -3x - 44
Y intercept = -44
Slope/m = -3 (aka) -3/1
Answer:
it's the last one.
Step-by-step explanation:
both of them have ÀF as part of their angle.
Answer:
really, hola adios si si si
Step-by-step explanation:
The answer is B) <span>(q - 2)(2p - 5r)
</span>2pq - 5qr + 10r - 4p = 2pq - 4p - 5qr + 10r
= 2pq - 4p - (5qr - 10r)
= 2p(q - 2) - 5r(q - 2)
= (q - 2)(2p - 5r)
Answer: (-∞,-1) ∪ (0,+∞)
Step-by-step explanation: The representation fog(x) is a representation of composite function, meaning one depends on the other.
In this case, fog(x) means:
fog(x) = f(g(x))
fog(x) = ![3(x+\frac{1}{x} )-\frac{1}{x+\frac{1}{x} } -4](https://tex.z-dn.net/?f=3%28x%2B%5Cfrac%7B1%7D%7Bx%7D%20%29-%5Cfrac%7B1%7D%7Bx%2B%5Cfrac%7B1%7D%7Bx%7D%20%7D%20-4)
![fog(x)=3x+\frac{3}{x} -\frac{1}{\frac{x^{2}+x}{x} } -4](https://tex.z-dn.net/?f=fog%28x%29%3D3x%2B%5Cfrac%7B3%7D%7Bx%7D%20-%5Cfrac%7B1%7D%7B%5Cfrac%7Bx%5E%7B2%7D%2Bx%7D%7Bx%7D%20%7D%20-4)
![fog(x)=3x+\frac{3}{x} -\frac{x}{x^{2}+x} -4](https://tex.z-dn.net/?f=fog%28x%29%3D3x%2B%5Cfrac%7B3%7D%7Bx%7D%20-%5Cfrac%7Bx%7D%7Bx%5E%7B2%7D%2Bx%7D%20-4)
![fog(x)=\frac{3x^{2}(x^{2}+x)+3(x^{2}+x)-x-4x(x^{2}+x)}{x(x^{2}+x)}](https://tex.z-dn.net/?f=fog%28x%29%3D%5Cfrac%7B3x%5E%7B2%7D%28x%5E%7B2%7D%2Bx%29%2B3%28x%5E%7B2%7D%2Bx%29-x-4x%28x%5E%7B2%7D%2Bx%29%7D%7Bx%28x%5E%7B2%7D%2Bx%29%7D)
![fog(x)=\frac{3x^{4}+3x^{3}+3x^{2}+3x-x-4x^{3}+4x^{2}}{x(x^{2}+x)}](https://tex.z-dn.net/?f=fog%28x%29%3D%5Cfrac%7B3x%5E%7B4%7D%2B3x%5E%7B3%7D%2B3x%5E%7B2%7D%2B3x-x-4x%5E%7B3%7D%2B4x%5E%7B2%7D%7D%7Bx%28x%5E%7B2%7D%2Bx%29%7D)
![fog(x)=\frac{3x^{4}-x^{3}-x^{2}+2x}{x(x^{2}+x)}](https://tex.z-dn.net/?f=fog%28x%29%3D%5Cfrac%7B3x%5E%7B4%7D-x%5E%7B3%7D-x%5E%7B2%7D%2B2x%7D%7Bx%28x%5E%7B2%7D%2Bx%29%7D)
This is the function fog(x).
The domain of a function is all the values the independent variable can assume.
For fog(x), denominator can be zero, so:
![x(x^{2}+x) \neq 0](https://tex.z-dn.net/?f=x%28x%5E%7B2%7D%2Bx%29%20%5Cneq%200)
If x = 0, the function doesn't exist.
![x^{2}+x \neq0](https://tex.z-dn.net/?f=x%5E%7B2%7D%2Bx%20%5Cneq0)
![x(x+1) \neq0](https://tex.z-dn.net/?f=x%28x%2B1%29%20%5Cneq0)
![x+1\neq0](https://tex.z-dn.net/?f=x%2B1%5Cneq0)
<u>Therefore, the domain of this function is: </u><u>-∞ < -1 or x > 0</u>